Parasitic manipulation of male sexual advertisement in Toxoplasma gondii- Rattus norvegicus association - Vasudevan, Anand (2016)
Parasitic manipulation of host behavior is often seen as exploitative in nature. An example is Toxoplasma gondii that has shown to alter the innate fear in rats toward cat odors, increasing its chances of transmission to complete its two-stage life cycle. In this thesis, I studied another behavioral manipulation in the reproductive domain. I show that T. gondii manipulates mate choice, causing females to prefer infected male rats and is also sexually transmissible. I demonstrated that this mate choice manipulation is due to Major Urinary Proteins (MUPs) and that infected rats had increased levels of MUPs. Moreover, MUPs is sufficient and necessary to attract females in a dose dependent manner. Finally, MUPs was shown to be dynamic and condition dependent on three factors- age, health and social environment. Thus, a parasite that can enhance reproductive opportunities of a host will benefit from blunted selection pressure from the host and gain advantage of transmission.